A molecular networking-based isolation of gardneria alkaloids from Gardneria distincta and their anti-inflammatory activity. (May 2023) - Teng, Sifan; He, Junjie; Wang, Xiaoqian; Li, Yiqian; Khan, Afsar; Zhao, Tianrui; Wang, Yudan; Cheng, Guiguang; Liu, Yaping
Abstract: Gardneria distincta P. T. Li is traditionally applied as a herbal medicine for treatment various ailments, and is mainly distributed in Southwestern China. Under the guided separation of MS/MS-based molecular networking, eight undescribed oxindole alkaloids, gardistines A-H, as well as 17 known alkaloids were discovered from the whole parts of Gardneria distincta. Structural elucidation of these undescribed alkaloids was performed by various spectroscopic methods. Gardistine A is a rare oxindole gardneria alkaloid bearing an ester carbonyl group attached to C-18, which is the second reported alkaloid of oxindole gardneria-type. All of the identified monoterpene indole alkaloids were investigated for their anti-inflammatory activity in LPS-induced RAW 264.7 cells. Gardistines A-B and akuammidine demonstrated significant inhibitory effects on the expressions of nitric oxide, tumor necrosis factor alpha, and interleukin-6 at 20 μM. Graphical abstract: Image 1 Highlights: Eight undescribed MIAs were obtained from Gardneria distincta based on a molecular networking strategy. Gardistines A was bearing an ester carbonyl group attached to C-18. Gardistines A-B and akuammidine showed significant anti-inflammatory activities.